(x ^ 2-5x-6) / (x ^ 3 + ax + 2 + bx + c) מפשט ל 1 / (x-2), ולאחר מכן + b + c =?

(x ^ 2-5x-6) / (x ^ 3 + ax + 2 + bx + c) מפשט ל 1 / (x-2), ולאחר מכן + b + c =?
Anonim

תשובה:

#a + b + c = 9 #

הסבר:

בהתחשב you # (x ^ 2-5x-6) / (x ^ 3 + ax ^ 2 + bx + c) = 1 / x-2 #

מכאן נובע:

# (x ^ 2-5x-6) (x-2) = x ^ 3 + ax ^ 2 + bx + c #

הכפל

#x (x ^ 2-5x-6) - 2 (x ^ 2-5x-6) = x ^ 3 + ax ^ 2 + bx + c #

# x ^ 3-5x ^ 2-6x - 2x ^ 2 + 10x + 12 = x ^ 3 + ax ^ 2 + bx + c #

שלב כמו מונחים:

# x ^ 3-7x ^ 2 + 4x + 12 = x ^ 3 + ax ^ 2 + bx + c #

מקדמי התאמה:

#a = -7, b = 4 ו- c = 12 #

#a + b + c = -7+ 4 + 12 #

#a + b + c = 9 #